Mencermati Teori Keadilan Sosial John Rawls - Soleh, A. Khudori (ULUL ALBAB Jurnal Studi Islam, 2004)
Rawls' justice theory is based on three basic concepts: concept of property from John Locke, social contract from Rousseau, and imperative categories from Kant. This Rawls' justice conception itself emerges as a respond for social injustice in society as well as i nequitable behavior affected by the ethics of utilitarianism. Furthermore, according to Rawls, justice is fairness. The principles of justice are, (1) equal and maximum feasible liberty for all, (2) power and wealth to be distributed equally, except where inequalities; would work for the adage of all and where all would have equal opportunity to attain the higher position. The first principle supposes as permanent principle and, which cannot be interpreted. On the other hand, the second principle degrades two formulas: (a) everyone’s  advantage (b) equally open. So forth, from formula (a) can be degraded two possibilities: principle of efficiency and principle of differentiation, whereas from formula (b) also can be degraded two possibilities: equality as careers open to talents and equality as equality of fair opportunity): Hencefonh, from possibility of (a) and (b) yielded four possibilities of justice interpretation: natural freedom, free equality, free aristocracy and the equality democratize.